Neoshirakia japonica (Siebold & Zucc.) Esser [Euphorbiaceae] fruit suppresses obesity and obesity-induced inflammation in adipocytes, macrophages, and obese mice - Lee, Eunbi; Park, Juhye; Nam, Ju-Ock (Frontiers in Pharmacology, 2025)
IntroductionThe objective of this study was to demonstrate the anti-obesity and anti-inflammatory effects of Neoshirakia japonica (Siebold & Zucc.) Esser [Euphorbiaceae] under obesity-induced conditions. Traditionally used in ethnopharmacology to dispel “wind-dampness” and “damp-heat,” these effects can be interpreted in modern medicine as chronic inflammation and metabolic imbalance associated with obesity.MethodsThe anti-obesity and anti-inflammatory potential of N. japonica fruit extract (NJFE) was evaluated in high-fat diet (HFD)-induced obese mice, 3T3-L1 adipocytes, and LPS-stimulated RAW264.7 macrophages. Mitochondrial function was assessed using MitoTracker fluorescence, and LC-MS analysis was performed to identify the chemical fingerprint and putative bioactive metabolites.ResultsIn HFD-induced obese mice, NJFE significantly reduced adipocyte hypertrophy, dyslipidemia, and glucose intolerance, while alleviating adipose tissue inflammation. In 3T3-L1 adipocytes, NJFE suppressed adipogenic differentiation and downregulated adipogenesis-related genes. In RAW264.7 macrophages stimulated with LPS, NJFE markedly reduced inflammatory responses. Furthermore, NJFE attenuated inflammatory responses in 3T3-L1 adipocytes exposed to conditioned medium derived from LPS-stimulated RAW264.7 cells. NJFE also improved mitochondrial function in adipocytes.ConclusionThese findings demonstrate that NJFE not only improves obesity but also alleviates obesity-induced inflammation, supporting its potential as a promising natural therapeutic candidate for the prevention and treatment of obesity and related metabolic disorders.